Spatial practices in the mobile network and the rise of individual power : a case study of the Sunflower Student Movement in Taiwan - Hsu, Che-Wei (2020)
This thesis chooses the Sunflower Student Movement as a case to analyze the mutual construction of power-knowledge relation in the social background of mobile communication-body relation. The Sunflower Student Movement was a civil protest composed of students, civic groups and the general public. The participants protested against the passing of the Cross-Strait Service Trade agreement at the Legislative Yuan. For the first time, protesters occupied the Taiwanese parliament. With the widespread of mobile devices (such as smartphones), the Sunflower Student Movement has marked a new form of resistance in the era of mobile communications. This study uses the discourse of the newspaper as the primary source of data. Based on Fairclough’s critical discourse analysis and Foucault’s power-knowledge relation, this case study explores three interrelated dimensions of society in Taiwan. The first part focuses on discussing Taiwan’s current political and economic environment to trace the relevance of social changes and generational conflicts. The second part mainly shows how the various combination of body and mobile devices creates specific spaces. This social phenomenon has transformed the meaning between space and place, blurring the boundary between virtual and physical space. The third part is an in-depth analysis of the manifestation of personal power in the movement. Individuals, as the subject and object of power, have complicated the resistance and monitoring strategies between government and the civic public with the innovation of mobile networks. This study argues that knowledge is constructed in specific social conditions at a given period. The multiple forms of discourse created during the Sunflower Student Movement influenced the collective consciousness of the public. Moreover, the evolution of mobile networks has changed the ways of knowledge dissemination. In this social context, the relationships between body, power, and knowledge have established a dynamic system of continuous transformation between citizens and government.